A statistical analysis of wind speed data used in installation of wind energy conversion systems - Akpinar, EK; Akpinar, S (Pergamon-Elsevier Science Ltd, 2005)
Wind speed is the most important parameter in the design and study of wind energy conversion systems. In this study, statistical methods were used to analyze the wind speed data of Keban-Elazig in the east region of Turkey. Measured hourly time series of wind speed data were obtained from the State Meteorological Station in Keban-Elazig over a five year period from 1998 to 2002. The probability density distributions are derived from the time series data and the distributional parameters are identified. Two probability density functions are fitted to the measured probability distributions on a yearly basis. (C) 2004 Elsevier Ltd. All rights reserved.
Keywords: Weibull distributions; Rayleigh distributions; Weibull parameter; wind speed data; wind energy